Pointers on how to produce a true-breeding herd of polled Herefords or Shorthorns. - Ibsen, H.L. (Kansas Agricultural Experiment Station, 2012)
It is a well-known fact that Aberdeen-Angus cattle breed true for the polled characteristic. By that I mean that they never produce a calf with horns. Sometimes a purebred Angus bull will have scurs, but from a genetic standpoint he is still considered a polled animal. Scurs are objectionable and could be bred out of the Angus breed if no scurred bulls were ever used for breeding purposes. Removing the scurs with caustic does not change a bull’s breeding qualities.
Keywords: Beef; True-breeding; Polled Herefords; Shorthorns; Scurs